XY female with complete androgen insensitivity syndrome with bilateral inguinal hernia - Baldiwala, Aafrin Shabbir; Lad, Vipul C. (International Surgery Journal, 2021)
The complete androgen insensitivity syndrome (AIS), previously called testicular feminization syndrome, is an X-linked recessive rare disorder. AIS is the most common male pseudohermaphrodite. Patient has 46, XY chromosome and testis. The individual is phenotypically female and genotypically male. Antimullerian hormone is produced by the testis. So, uterus and fallopian tubes do not develop in fetus. The fault lies with androgen receptors which are mutated. Male differentiation of external genitals does not occur. The individuals are reared as girls and the condition is suspected when the individual is evaluated for primary amenorrhea, infertility or when unilateral/bilateral inguinal hernia is diagnosed in girls. This disorder includes a spectrum of changes ranging from male infertility to completely normal female external genitalia in a chromosomally male individual. These cases need proper diagnosis and appropriate management. We report this case for its interesting presentation. The patient is a 23 year old female, presented with bilateral labial swellings and primary amenorrhoea. Subsequent investigations were done which revealed that the patient is a genetically male with absence of female internal genitalia but presence of testes. Proper psychological support was also given to her, which is more important.